A comparative study of anxiety symptoms in Chinese and Rwandan adolescents: a cross-cultural measurement invariance study of the GAD-7 scale - Niwenahisemo, Lisa Cynthia; Zhang, Qi; Wang, Wo; Geng, Dan-dan; Xu, He-yan; Hu, Jin-hui; Ma, Ling-li; Tan, Jian-yu; Kong, Yi-ting; Hong, Su; Kuang, Li (Frontiers in Psychiatry, 2025)
IntroductionCultural factors and assessment methods significantly influence how anxiety symptoms are expressed and reported. However, few cross-cultural studies have employed culturally appropriate and validated tools, and even fewer have provided substantial comparisons across different groups with diverse cultural backgrounds. This study aimed to assess the measurement invariance of the GAD-7 scale across Chinese and Rwandese adolescents, enabling reliable cross-cultural comparisons.MethodsThis study included 2017 Chinese adolescents and 1813 Rwandan adolescents. Cronbach’s alpha, exploratory factor analysis (EFA), and multiple group confirmatory factor analysis (MGCFA) were used to assess the validity of the GAD-7 scale across the two groups. Measurement invariance testing was employed to investigate cross-cultural equivalence.ResultsThe GAD-7 demonstrated good psychometric properties. CFA supported a one-factor model for the GAD-7 in both samples, though model fit indices varied. Measurement invariance testing confirmed configural and metric invariance but found partial scalar invariance. A latent mean comparison indicated a trend toward higher anxiety levels in Rwandan adolescents compared to Chinese adolescents, though the difference was not statistically significant (z = 0.02, d = 0.033, p = 0.98).DiscussionThe GAD-7 showed reliability in measuring generalized anxiety in both Chinese and Rwandese adolescents, confirming its cross-cultural construct validity. However, partial scalar invariance suggests that while the GAD-7 effectively detects anxiety symptoms, the severity of reported symptoms may not be directly comparable across cultures due to response patterns and possible linguistic factors. These findings highlight the importance of culturally sensitive instruments for accurate anxiety assessment and expand evidence on reliable symptom screening and treatment monitoring across diverse populations.